(NfRANCUZKAQ mUZYKA hh WEKAs (NISTORIQs - (Ng(B.(N{NEERSONs; (Ng(B.(NpRIBEGINAs (NREDAKTORs ((NmOSKWAs (NmUZYKAs, 1970)
(NnAU^NO(B-(NPOPULQRNAQ MONOGRAFIQ POSWQ]ENA RASSMOTRENNI@ WAVNEJ[IH TENDENCIJ W RAZWITII FRANCUZSKOJ MUZYKI hh WEKA(B. s
Keywords: (NISTORIQs